PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA 3 PERUSAHAAN TELEKOMUNIKASI BESAR DI INDONESIA - Noviyanti, Fitri; Maharany, Salsabila; Zahroh, Maidatus; Cahyaningrum, Arfenita; Suparta, I Made (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2025)
The purpose of this study was to analyze the effect of liquidation and solvency on firm value with profitability as an intervening variable in three large telecommunications companies in Indonesia, namely PT Telkom Indonesia Tbk, PT Indosat Tbk, and PT XL Axiata Tbk. This study uses quantitative methods and uses secondary data from the financial statements of 3 companies in 2015-2023.  The results showed that the liquidity variable has a negative and significant effect on firm value because the significance value of the liquidity variable is smaller than 0.05. Meanwhile, the solvency variable does not have a significant effect on firm value, because the significance value of the solvency variable is greater than the value of 0.05